Criminal Law Enforcement on Digital Identity Misuse in AI Era for Commercial Interests in Indonesia - Dwiandari, Ameena Syifa; Arifin, Ridwan (Universitas Negeri Semarang, 2025)
The rapid development of Artificial Intelligence (AI) technology particularly in the forms of deepfakes and voice cloning has significantly impacted the lives of Indonesians. While AI offers various conveniences and innovations, it also poses serious threats, especially the misuse of digital identities for commercial purposes. This study aims to analyze the adequacy and effectiveness of Indonesia's criminal law, particularly the Indonesian Criminal Code and Law No. 11 of 2008 on Electronic Information and Transactions (ITE Law), in addressing AI-based digital identity crimes. Using a normative juridical approach, this research finds that current legal frameworks do not specifically regulate AI-related offenses. As a result, perpetrators often exploit legal and technological loopholes to avoid prosecution. The consequences of these crimes are far-reaching, including financial losses, reputational damage, and psychological trauma for victims. The study recommends revising the ITE Law, strengthening personal data protection, forming an AI-based digital forensics task force, and fostering cross-sectoral collaboration to combat digital identity crimes without stifling technological innovation.